The Effectiveness of Using Role Play to Teach Speaking ( A Pre-Experimental Study at Class VII A of SMPN 1 Jombang ) - Junaidi, Abdul Khosim; Agustina, Ria Kamilah (Bilingua, 2025)
This research aims to investigate the effectiveness of using the Role Play method to improve the speaking skills of Grade VII A students at SMPN 1 Jombang in the academic year 2024/2025. This study employed a quantitative approach with a one-group pre-test and posttest pre-experimental design. The sample consisted of 32 students. Data were collected through speaking tests administered before and after the treatment (role play) and analyzed using a paired sample ttest. The results showed an increase in the average score from 65.66 (pre-test) to 81.00 (post-test). The t-test revealed a significance value of < 0.001, indicating a statistically significant difference between students' speaking ability before and after being taught using the Role Play method. Therefore, it can be concluded that Role Play is effective in enhancing students' speaking skills.